The Role of Caseworkers in Unemployment Insurance: Evidence from Unplanned Absences - Amelie Schiprowski (Institute of Labor Economics (IZA), 2017)
Caseworkers are the main human resource used to provide social services. This paper asks if, and how much, caseworkers matter for the outcomes of unemployed individuals. Using large-scale administrative data, I exploit exogenous variation in unplanned absences among Swiss UI caseworkers. I find that individuals who lose an early meeting with their caseworker stay on average 10 days longer in unemployment (5% relative to the mean). Results show large heterogeneity in the economic value of caseworkers: the effect of a foregone meeting doubles for caseworkers in the highest productivity tercile, while it is zero for caseworkers in the lowest tercile. Finally, absences induce negative spillover effects on the performance of present colleagues, who have to cover additional workload.
Keywords: J64; J65; M50; 330; unemployment insurance; public human resources; caseworkers